Lao People's Democratic Republic : Staff Report and Public Information Notice. (IMF Staff Country Reports; Country Report ;, 2011)
Recent economic development and outlook of Lao are discussed in this study. However, the economy continued to exceed its macroeconomic speed limit in 2009, putting pressure on the balance of payments. The outlook for GDP growth in 2010 is favorable and inflation is likely to remain moderate. Discussions centered on policies required to maintain near-term macroeconomic stability and stem the decline in net foreign assets (NFA) of the banking system. IMF staff noted that the overall fiscal deficit should be put on a medium-term consolidation path.